EXPERIENCE OF MINORITY SEXUAL GROUP IN MALAYSIA: THE RELATIONSHIP BETWEEN PERCEIVED DISCRIMINATION AND PSYCHOLOGICAL WELL-BEING - Mohd Firdaus Ninam Shah; Qarem Mohamed Mustafa (Journal of Islamic, Social, Economics and Development, 2022)
Even though same sex romantic relationship or homosexual relationship is not accepted in Malaysia, the numbers of homosexual males are expected to increase based on the participation of an annual sexuality rights festival named â€œSeksualiti Merdekaâ€ which started in 2008. There are several studies in Malaysia that describe the challenges faced by sexual minority groups namely being discriminated upon which also put their psychological wellbeing at risks. The current study aims to identify the relationship between sociodemographic variables, perceived discrimination, and psychological well-being among homosexuals male in Malaysia. Based on purposive sampling, a total of 136 Malaysian gay men were purposively recruited through social media outlets, as well as email by responding to a link created for the online survey measuring perceived discrimination and presence of psychological distress. Pearson correlation analysis indicates a significant negative relationship between age and educational background with psychological distress while a significant positive relationship between perceived discrimination and psychological distress specifically symptoms of somatization, anxiety, and depression. Moreover, multiple regression suggests perceived discrimination to significantly predict the presence of psychological distress. These highlight the importance of exploring the experience of homosexuals male in Malaysia since the challenges of each sexual minority group is unique.